Determinants of Financial Reporting Quality: Evidence from Local Governments in Sumatera Island - Aurelia, Clara; Nurmayanti, Poppy; Afifah, Ulfa; Setiawan, Doddy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to investigate determinants of financial reporting quality (FRQ) local government in Sumatera Islands, Indonesia. The FRQ local government is proxied by audit opinion from the Indonesian Supreme Audit Board (ISAB) for each local government sample. The tested independent variables are capital expenditure, characteristics of local governments (size, financial independency, and local government status), and mayors characteristics (experience and age). Data were obtained from the summary of semester audit results of ISAB, official website of the ministry of finance and the local governments in Sumatera Island. Total samples are 143 local governments and the period of study is 5 years (2016 2020, or 715 observations). Using the multinomial logistic regression, this study found that a lower ratio of capital expenditure, smaller local governments, local government in city areas, and local governments led by older and experienced mayor are associated with higher financial reporting quality. This study also uncovered that mayor education level and mayor graduated from the Institute of Public Administration (or IPDN) have positive influence of financial reporting quality of the local governments.